Causality Analysis of Indonesia's External Debt with Vector Autoregression (VAR) Approach - Sri Yanti Aisyah Lubis; Arbanur Rasyid; Budi Gautama Siregar (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
The Indonesian government faces significant problems in terms of development funding due to the lack of adequate financial resources. Therefore, as a developing country, Indonesia is forced to take action by spending a large amount of money to promote growth and implement various development initiatives through foreign debt policies. The formulation of this research problem is whether there is an interaction relationship between exports, imports, inflation, exchange rates and foreign exchange reserves with Indonesia's foreign debt. This study aims to analyze the interaction relationship between exports, imports, inflation, exchange rates and foreign exchange reserves with Indonesia's foreign debt. This research was conducted using quantitative research methods. The sampling technique used is purposive sampling with the number of samples to be taken based on an assessment of the completeness of this research data, namely from 2015 to 2022 there are 96 samples. The research method uses the Vector Autoregression (VAR) approach using the Eviews 12 program. The Granger test shows that there is no two-way causality relationship between exports, imports, inflation, exchange rates and foreign exchange reserves with Indonesia's external debt. However, there is cointegration in the study so that there is an interaction relationship between exports, imports, inflation, exchange rates and foreign exchange reserves with Indonesia's external debt. Given the complexity of the relationship between Indonesia's external debt and the variables of exports, imports, inflation, exchange rates, and foreign exchange reserves, regional and international cooperation is also important. The government can establish partnerships with other countries to increase trade, manage financial risks, and strengthen mutually supportive policy frameworks.